PENGARUH KONSENTRASI KEPEMILIKAN KELUARGA DAN INTERNET FINANCIAL REPORTING (IFR) TERHADAP ASIMETRI INFORMASI - Virgiawan, I Putu Yogi; Diyanty, Vera (UI Scholars Hub, 2015)
This study examines whether family-controlled firms have a higher level of information asymmetry than non family-controlled firms. This study also examines the influence of Internet Financial Reporting (IFR) to the information asymmetry. The results of the study indicate that family-controlled firms do not have higher level of information asymmetry than non family-controlled firms. Moreover, the study found that the application of IFR reduces the level of firm’s information asymmetry. This study contributes to the accounting literature and regulator by providing evidence the role of IFR in reducing information asymmetry.